PENINGKATAN PRESTASI BELAJAR IPS MENGGUNAKAN MEDIA KARTU BERGAMBAR (DRAW CARD) - Nurlaili Dina Hafni (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
To upgrade learning achievement in Social Studies (IPS), the authors use the media with picture cards (Draw Card), the authors choose picture cards because these media are common media and easy to understand by students. This media also has the aim of attracting students' attention, clarifying the material, illustrating facts or information that will be quickly understood if illustrated with pictures. In addition, drawing card media (Draw Card) can be made easily and used according to the creativity of educators based on the material to be delivered.After observing and evaluating, the progress of students in the study of Increasing Learning Achievement in Social Studies (IPS) Using Picture Card Media (Draw Card) in class VI students of SDN Tasikmadu 02 Palang District, Tuban Regency. It can be concluded as follows (1) The application of illustrated card media (Draw Card) can be carried out properly and structured by researchers, implementation activities are carried out through pre-cycle activities, then cycle I and continues in cycle II. (2) Student achievement continues to show a significant increase compared to before using the media, student achievement tends to be low, namely 0 or no students who complete the minimum completeness criteria that have been set. It can be seen that the social studies learning achievement of 18 students, there are 18 students or 100% who get a complete score (T) and 0 students or 0% of students get an incomplete score (TT). His class average is 90. (3) Social Studies (IPS) learning achievement by using drawing card media (Draw Card) has increased which can be seen from the average value and classical completeness presentation, the pre-cycle value shows an average of 53.89% with the percentage of students who complete 0%. After the implementation of the picture card media in the first cycle, the formative test results reached 70% with the percentage of students who completed 9 and students who did not complete 9, in the second cycle an average increase of 90% and has reached the indicator of success of classical completeness, namely at least 85% of the total number of students. This shows that the use of picture card media (Draw Card) can improve Social Studies learning achievement.